Transformasi Digital Moneter: Analisis Komprehensif Implementasi Central Bank Digital Currency (CBDC) dan Implikasinya Terhadap Stabilitas Sistem Keuangan - Imama Zuchroh; Regina Septi Wanti Bere; Kristina Gemma Galgani; Grace Imanuela Lay Rihi; Budi Cahyono (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This study examines the phenomenon of Central Bank Digital Currency (CBDC) as a technological innovation that changes the landscape of the global monetary system. In the midst of the rapid development of digital technology and cryptocurrencies, central banks in various countries are starting to consider and develop their own digital currencies. This study aims to comprehensively analyze the aspects of CBDC implementation, including its potential benefits, challenges, and impact on financial system stability and monetary policy. Through a descriptive qualitative approach with a literature study method, this study explores various dimensions of CBDC, including technological architecture, implementation models, and its socio-economic implications. The results of the study show that CBDCs have significant potential in improving the efficiency of the payment system, encouraging financial inclusion, and strengthening the transmission of monetary policy. However, its implementation also presents serious challenges related to data privacy, cybersecurity, and the stability of the banking system. This study makes an important contribution to a comprehensive understanding of CBDCs and their implications for the future of the global financial system.